Syazaliyana Razanabihah earns UMPSA 2024 Inspirational Alumni Icon Award - Naqiah, Puaad (UMPSA, 2025)
GAMBANG, 16 April 2025 – The 2024 Mercu Sanjung Awards Night (MARS) at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) witnessed the recognition of outstanding alumni contributions when Syazaliyana Razanabihah Surahman was announced as the recipient of the Inspirational Alumni Icon Award, for her remarkable achievements in entrepreneurship and her strong commitment to student welfare.